Diverse tick-borne microorganisms identified in free-living ungulates in Slovakia - Kazimirová, Mária (2018)
Background: Free-living ungulates are hosts of ixodid ticks and reservoirs of tick-borne microorganisms in central Europe and many regions around the world. Tissue samples and engorged ticks were obtained from roe deer, red deer, fallow deer, mouflon, and wild boar hunted in deciduous forests of south-western Slovakia. DNA isolated from these samples was screened for the presence of tick-borne microorganisms by PCR-based methods. Results: Ticks were found to infest all examined ungulate species. The principal infesting tick was Ixodes ricinus, identified on 90.4% of wildlife, and included all developmental stages. Larvae and nymphs of Haemaphysalis concinna were feeding on 9.6% of wildlife. Two specimens of Dermacentor reticulatus were also identified. Ungulates were positive for A. phagocytophilum and Theileria spp. Anaplasma phagocytophilum was found to infect 96.1% of cervids, 88.9% of mouflon, and 28.2% of wild boar, whereas Theileria spp. was detected only in cervids (94.6%). Importantly, a high rate of cervids (89%) showed mixed infections with both these microorganisms. In addition to A. phagocytophilum and Theileria spp., Rickettsia helvetica, R. monacensis, unidentified Rickettsia sp., Coxiella burnetii, “Candidatus Neoehrlichia mikurensis”, Borrelia burgdorferi (s.l.) and Babesia venatorum were identified in engorged I. ricinus. Furthermore, A. phagocytophilum, Babesia spp. and Theileria spp. were detected in engorged H. concinna. Analysis of 16S rRNA and groEL gene sequences revealed the presence of five and two A. phagocytophilum variants, respectively, among which sequences identified in wild boar showed identity to the sequence of the causative agent of human granulocytic anaplasmosis (HGA). Phylogenetic analysis of Theileria 18S rRNA gene sequences amplified from cervids and engorged I. ricinus ticks segregated jointly with sequences of T. capreoli isolates into a moderately supported monophyletic clade. Conclusions: The findings indicate that free-living ungulates are reservoirs for A. phagocytophilum and Theileria spp. and engorged ixodid ticks attached to ungulates are good sentinels for the presence of agents of public and veterinary concern. Further analyses of the A. phagocytophilum genetic variants and Theileria species and their associations with vector ticks and free-living ungulates are required.